Sensitivity of Four Various Candida Species to Photodynamic Therapy Mediated by Indocyanine Green, an in vitro Study - Atefeh Tavangar; Faezeh Khozeimeh; Mehdi Razzaghi-Abyaneh; Safieh Sherkat (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Various species of candida contribute to oral candidiasis. It is the time to shift from conventional rigid antimicrobial therapies to more patient specific and safer ones. Purpose: The present study aimed to investigate antifungal effects of photodynamic therapy (PDT) using Indocyanine green as photosensitizer and low-power laser irradiation on the viability of candida albicans, candida tropicalis, candida glabrata and candida krusei, and to compare it with Nystatin as the conventional treatment. Materials and Method: In this in vitro study, 0.5 McFarland suspensions of candida's species were prepared (n=50, each). Each strain was then divided into five groups of 10 samples each, according to the following experimental interventions: (1) Nystatin, (2) photodynamic therapy: laser irradiation (wavelength= 808 nm, power= 100 mW, energy density= 10 J/cm2, exposure duration= 100 s) in the presence of the photosensitizer, (3) laser irradiation alone, (4) treatment with the PS alone and (5-control: no exposure to laser light or photosensitizer. Next, serial dilutions were prepared and seeded onto Sabouraud dextrose agar. The colonies were counted, and the values of log (CFU/ml) were analyzed by variance and the Tamhan test (p< 0.05). Results: Photodynamic therapy mediated indocyanine green is significantly effective in reducing the number of CFU/ml of all species of candida tested, compared to control group (p< .001). Nystatin, laser irradiation and photodynamic therapy, with respectively decreasing potency, have considerably reduced the number of candida's colonies in all four bacterial strains (p<. 05). Photosensitizer alone, showed impressive antimicrobial potency against all species of candida except candida albicans, in comparison to control group. Conclusion: It seems that laser therapy alone is more powerful than photodynamic therapy mediated indocyanine green; however, conventional treatment has still the top antimicrobial efficacy towards all candida species.